مسندامام احمدبن حنبل میں مخضرمین راویان ِحدیث : تعارفی جائزہ - SAJID MAHMOOD; SAMI UL HAQ (الضحی, 2021)
Sunnah is second authentic source of Islamic law. It is the one of the real blessing of Allah that He created religious scholars and aeimma for writing, memorizing, defending and Rawayat wa darayat of these sunah .The struggles and services of Imam Ahmad bin Hanbal (Rahimahu Allahu Ta'ala) for Ahadees are praise working.He was born in Marw on the 20th of Rabi-ul-Awwal 164 A.H.He was a very pious scholar who devoted all his life in the Science of Ahadith and Fiqh.He wrote many books but His most famous book is his "MUSNAD".A book in which he collected about 50 000 to 70 000 Ahadith. His book Musnad Ahmad bin Hanbal is a true treasure of knowledge.This book has many qualities, one of the distinctive quality of this book is that Mukhzramen-e-Rawat have been mentioned here.